2021
DOI: 10.1038/s10038-021-00987-x
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant of SHARPIN confers increased risk of late-onset Alzheimer’s disease

Abstract: Late-onset Alzheimer’s disease (LOAD) is the most common form of dementia, and its pathogenesis is multifactorial. We previously reported a rare functional variant of SHARPIN (rs572750141, NP_112236.3:p.Gly186Arg) that was significantly associated with LOAD. In addition, several recent studies have suggested the potential role of SHARPIN in AD pathogenesis. In this study, we sought to identify additional functional variants of SHARPIN in Japanese population. Six highly deleterious variants of SHARPIN, comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In a follow-up study, six more SHARPIN variants were identified from a cohort of 180 patients with LOAD and 184 patients with mild cognitive impairment ( Table 1 ). This, at present, is the only reported association between SHARPIN mutation and human diseases [ 59 ].…”
Section: Lubacmentioning
confidence: 98%
“…In a follow-up study, six more SHARPIN variants were identified from a cohort of 180 patients with LOAD and 184 patients with mild cognitive impairment ( Table 1 ). This, at present, is the only reported association between SHARPIN mutation and human diseases [ 59 ].…”
Section: Lubacmentioning
confidence: 98%
“…Most of the AD-associated SHARPIN variants cause amino acid replacements, whereas the AD-associated RBCK1 SNP (rs1358782) is an intron variant ( Bellenguez et al, 2022 ). Among them, the G186R and R274W variants of SHARPIN reportedly suppressed TNF-α-mediated NF-κB activation and generated aberrant granular clumps in HEK293T cells ( Asanomi et al, 2019 ; Asanomi et al, 2022 ). Moreover, the R274W variant of SHARPIN shows a weaker interaction with HOIP ( Park et al, 2021 ).…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
“…Due to these effects, the G186R mutation of SHARPIN would impair the formation of the LUBAC complex. Since the G186R mutation of SHARPIN reportedly resulted in aberrant intracellular localization and attenuated NF-κB activation ( Asanomi et al, 2019 ; Asanomi et al, 2022 ), the G186R mutation may cause dissociation of the LUBAC complex, and then the destabilized SHARPIN could form aggregates in the cell.…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The heritability of AD—that is, the presence of genetic risk factors—is estimated to be 60% to 80% 11 . A large number of genetic factors undoubtedly contribute to the etiopathogenesis and progression of AD, and some of them have been identified via whole-genome sequencing analyses 12 , 13 and genome-wide association studies 14 16 . The AD risk genes are implicated in the immune response ( CLU, CR1, CD33, EPHA1, MS4A4E/MS4A6A, ABCA7, PTK2B, TREM2 , and TREML2 ), endocytosis ( BIN1, PICALM , and CD2AP ), and lipid processing ( APOE, ABCA7 , and SORL1 ) 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%